2022
DOI: 10.1021/acs.molpharmaceut.2c00763
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Porous Silicon Nanocarrier for Glioblastoma Treatment

Abstract: Clinical treatment of glioblastoma (GBM) remains a major challenge because of the blood−brain barrier, chemotherapeutic resistance, and aggressive tumor metastasis. The development of advanced nanoplatforms that can efficiently deliver drugs and gene therapies across the BBB to the brain tumors is urgently needed. The protein "downregulated in renal cell carcinoma" (DRR) is one of the key drivers of GBM invasion. Here, we engineered porous silicon nanoparticles (pSiNPs) with antisense oligonucleotide (AON) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Using an innovative microfluidic BBB/GBM organ-on-a-chip model, the ability of our developed cubosomes to cross the BBB tight monolayer and then the uptake into glioblastoma U87 cells was investigated under physiological flow conditions. The microfluidic model was developed using a previously reported method , with slight modifications, as presented in Figure A. This model is designed to closely mimic the physiological complexity of the BBB .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using an innovative microfluidic BBB/GBM organ-on-a-chip model, the ability of our developed cubosomes to cross the BBB tight monolayer and then the uptake into glioblastoma U87 cells was investigated under physiological flow conditions. The microfluidic model was developed using a previously reported method , with slight modifications, as presented in Figure A. This model is designed to closely mimic the physiological complexity of the BBB .…”
Section: Resultsmentioning
confidence: 99%
“…To further assess the permeability of the developed cubosomes across the BBB and the subsequent uptake into brain cancer cells, we used a μBBB-GBM model, which was previously developed and validated by previous studies. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineered porous silicon nanoparticle conjugated antisense oligonucleotides as a targeted drug delivery system for the clinical treatment of glioblastoma have been attempted . Glioblastoma is an aggressive tumor that originates in the brain.…”
Section: Dendrimersmentioning
confidence: 99%
“…The ability of the proposed antisenseloaded nanocarrier to penetrate the BBB network was demonstrated using a microfluidic-based BBB model and xenograft mouse models (Figure 2). 22 The size of the nanocarrier is essential for improving cancertargeting efficiency and biodistribution. Liaw et al have demonstrated the effect of nanocarrier size on brain tumor targeting efficiency and BBB penetrating capability.…”
Section: Dendrimersmentioning
confidence: 99%